New religious trends in studies of Ukrainian scholars - Fylypovyč, Ljudmyla Oleksandrivna (Ukrai͏̈ns'ke relihijeznavstvo, 2006)
Considering the fifteen years of experience in studying NRT in Ukraine, it should be noted that the interest in the new in religion has always been and will be sustainable, and the study of these innovations will never lose its relevance. Due to the specificity of the object itself (unknown, exotic, heterogeneous) in its estimations there will be ambiguity, polysyllosity, heterogeneity, alternatives, etc., that is, all that characterizes the modern literature on new religions.